ANALISIS KEUNGGULAN PERUSAHAAN KELUARGA MENGGUNAKAN PENDEKATAN DNA GROWTH FAMILY BUSINESSES (Studi Kasus Pada PT.Kanaya) - Tri Kharisma Aldityo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This objective of this study is to determine the core competence of PT. Kanaya, a family business in the province of Jakarta. This descriptive research was held from June to November 2017 using qualitative approach to identify the core competence of the company and its position among closest competitors so the company can develop their future strategy. This study uses VRIO Framework with DNA Growth Family Businesses approach to identify the company’s core competence and Competitive Profile Matrix (CPM) to benchmark its key factors with its closest competitors resulting from VRIO. The conclusion is that PT. Kanaya has 20 company advantages that can be generalized to 11 key factors. Furthermore, the benchmarking indicates that the company has a marginal advantage over its competitors. To achieve greater advantage, the company’s CSR activities should be relevant to their business operation, such as mangrove and coral cultivation, since the company works in marine field. The company should also increase their preference to environmentally friendly technology, such as the use of energy efficient and environmentally friendly ships.Keywords: family business, VRIO framework, CPM, DNA growth family businesses, qualitative